Freedom, Commerce, Bodies, Harm: The Case of Backpage.com - Swanson, Elizabeth (Social Inclusion, 2017)
This article situates lawsuits against Backpage.com in the context of changing laws and norms of sexual commerce and trafficking, and of evolving legal interpretations of Section 230 of the Communications Decency Act. Section 230 has been used repeatedly to shield internet service providers such as Backpage.com from liability for content generated by third parties that has led to criminal harm to others; in this case, the trafficking and commercial sexual exploitation of minors. Moving to a critique of the law as at times grievously detached from the realities it addresses, I compare the legal strategies and decisions in three prominent cases brought against Backpage.com in St. Louis, Tacoma, and Boston, respectively. This critique identifies the evacuation of gendered bodies and the harm done to them from the court opinions as an example of what Robert Cover has called the "interpretive violence" of the law, and of the judges who interpret and dispense it. I conclude by calling for courts and Congress to act together to disrupt the accumulation of interpretive precedent favoring freedom of commerce and speech over the protection of bodies from harm.